Atmospheric pollutants in Chiang Mai (Thailand) over a five-year period (2005-2009), their possible sources and relation to air mass movement - Chantara S. (2014)
Monitoring and analysis of the chemical composition of air pollutants were conducted over a five-year period (2005-2009) in the sub-urban area of Chiang Mai, Thailand. This study aims to determine the seasonal variation of atmospheric ion species and gases, examine their correlations, identify possible sources and assess major air-flow patterns to the receptor. The dominant gas and particulate pollutants were NH 3 (43-58%) and SO42- (39-48%), respectively. The annual mean concentrations of NH 3 (μg m -3) in descending order were 4.08 (2009) > 3.32 (2007) > 2.68 (2008) > 2.47 (2006) and 1.87 (2005), while those of SO42- (μg m -3) were 2.60 (2007) > 2.20 (2006) > 1.95 (2009) > 1.75 (2008) and 1.26 (2005). Concentrations of particulate ions were analyzed by principle component analysis to find out the possible sources of air pollutants in this area. The first component of each year had a high loading of SO42- and NH4+, which probably came from fuel combustion and agricultural activity, respectively. K +, a tracer of biomass burning, also contributed to the first or the second components of each year. Concentrations of NH4+ and SO42- were well correlated (r > 0.777, p < 0.01), which lead to the conclusion that (NH 4) 2SO 4 was a major compound present in this area. The 3-day backward trajectories of air mass arriving at Chiang Mai from 2005 to 2009 were analyzed using the hybrid single particle langrangian integrated trajectory (HYSPLIT) model and grouped by cluster analysis. The air mass data was analyzed for the dry season (n = 18; 100%). The trajectory of air mass in 2005 mainly originated locally (67%). In 2006, the recorded data showed that 56% of air mass was emitted from the western continental region of Thailand. In 2007, the percent ratios from the western and eastern continental areas were equal (39%). In 2008, 67% originated from the western continental area. In 2009, the recorded air mass mainly came from the western continental area (72%). In conclusion, the major trajectories of air mass from 2006 to 2009 originated from the southwest direction of the receptor, but in 2005, the air mass appeared to be locally originated. © 2012 Elsevier Ltd.